2020
DOI: 10.1038/s41598-020-70261-1
|View full text |Cite
|
Sign up to set email alerts
|

A study on the response of FRET based DNA aptasensors in intracellular environment

Abstract: this paper presents a study of the response of fRet based DnA aptasensors in the intracellular environment. Herein, we extend previous studies of aptasensors functioning in the extracellular environment to detection of antigens in the intracellular environment. An essential step in this research is the use of a novel means of achieving the endocytosis of aptasensors. Specifically, it is demonstrated that functioning aptasensors are successfully endocytosed by functionalizing the aptasensors with endocytosis-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This system can recognize and imaging prostate cancer cells that express prostate specific membrane antigen (PSMA) protein through delivery of Dox via activation of fluorescence QD. Recently, FRET aptasensors synthesized by conjugating Apt–QDs–AuNPs have been used for the detection of Staphylococcus aureus [ 60 ] and Tumor Necrosis Factor-alpha (TNF-α) [ 61 ]. The authors observed that selective binding occurred with limit of detection of 2 cfu/mL for S. aureus and strong fluorescence of an aptamer–QD conjugated donor was successfully quenched by an AuNPs acceptor in the presence of target molecules.…”
Section: Nanomaterials Based Aptamer Sensors As Diagnostic Toolmentioning
confidence: 99%
“…This system can recognize and imaging prostate cancer cells that express prostate specific membrane antigen (PSMA) protein through delivery of Dox via activation of fluorescence QD. Recently, FRET aptasensors synthesized by conjugating Apt–QDs–AuNPs have been used for the detection of Staphylococcus aureus [ 60 ] and Tumor Necrosis Factor-alpha (TNF-α) [ 61 ]. The authors observed that selective binding occurred with limit of detection of 2 cfu/mL for S. aureus and strong fluorescence of an aptamer–QD conjugated donor was successfully quenched by an AuNPs acceptor in the presence of target molecules.…”
Section: Nanomaterials Based Aptamer Sensors As Diagnostic Toolmentioning
confidence: 99%
“…Ghosh group developed an aptasensor for TNF-α detection based on FRET in an intracellular environment. The sensor was designed to enable cell-penetrating peptide-induced endocytosis, representing a novel measurement method [71].…”
Section: Fluorescencementioning
confidence: 99%
“…Its broad wavelength absorption spectrum allows PL to be excited in multiple QDs with different colors by a single excitation source. Owing to its broad wavelength absorption spectrum, the QD can utilize distance-dependent energy transfer phenomena, such as fluorescence resonance energy transfer (FRET) and nano surface energy transfer (NSET), through the introduction of other NPs such as AuNP as acceptors [34][35][36]. The high quantum yield of QDs result in high brightness and photochemical stability, making them resistant to chemical and photo degradation [37].…”
Section: Qd As Sensing Materialsmentioning
confidence: 99%
“…The second system is based on the materials directly attaching to the aptamer [34,35]. This strategy usually harnesses the distance-dependent energy transfer mechanism.…”
Section: Qd As Sensing Materialsmentioning
confidence: 99%
See 1 more Smart Citation